Acute Heart Failure in a Pregnant Woman with Preeclampsia: a Rare Case of Takotsubo Syndrome - S. A. Boldueva; D. S. Evdokimov; M. V. Rozhdestvenskaya; E. A. Rukoyatkina (Столичная издательская компания, 2022)
The mechanisms of takotsubo syndrome, better known as stress-induced cardiomyopathy, are not fully understood. The article presents a clinical case of the development of acute left ventricular failure in a 39-year-old pregnancy against the background of severe preeclampsia. Echocardiography revealed a decrease in global myocardial contractility, hypo-akinesia of the apex and all median parts of the left ventricle, hyperkinesis of the basal parts. After 2 weeks, myocardial contractility was normal, no contractility impairment was found. Two months after the acute episode of the disease, magnetic resonance imaging of the heart was performed, according to which no pathological changes were detected. Based on the clinical picture, electrocardiogram changes, laboratory data and typical transient echocardiographic changes, it was suggested that the patient had takotsubo syndrome.